2021
DOI: 10.1002/lt.26264
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib Efficacy After Sorafenib in Patients With Recurrent Hepatocellular Carcinoma After Liver Transplantation: A Retrospective Study

Abstract: Safety of regorafenib in hepatocellular carcinoma (HCC) recurrence after liver transplantation (LT) has been recently demonstrated. We aimed to assess the survival benefit of regorafenib compared with best supportive care (BSC) in LT patients after sorafenib discontinuation. This observational multicenter retrospective study included LT patients with HCC recurrence who discontinued first‐line sorafenib. Group 1 comprised regorafenib‐treated patients, whereas the control group was selected among patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…In patients progressing while on treatment with sorafenib, regorafenib in second-line setting may be an option [168]. It proved to be a safe and tolerable treatment in a preliminary evaluation [169], and very recently a multicenter retrospective cohort study including 81 patients (36 treated with regorafenib and 45 undergoing BSC at sorafenib discontinuation) confirmed these findings [170]. From sorafenib discontinuation, regorafenib was able to provide a significantly longer OS compared to BSC (13.1 vs. 5.5 months, p = 0.002) and was independently associated with lower mortality (HR = 0.37, 95% CI 0.16-0.89) [170].…”
Section: Systemic Therapiesmentioning
confidence: 89%
See 1 more Smart Citation
“…In patients progressing while on treatment with sorafenib, regorafenib in second-line setting may be an option [168]. It proved to be a safe and tolerable treatment in a preliminary evaluation [169], and very recently a multicenter retrospective cohort study including 81 patients (36 treated with regorafenib and 45 undergoing BSC at sorafenib discontinuation) confirmed these findings [170]. From sorafenib discontinuation, regorafenib was able to provide a significantly longer OS compared to BSC (13.1 vs. 5.5 months, p = 0.002) and was independently associated with lower mortality (HR = 0.37, 95% CI 0.16-0.89) [170].…”
Section: Systemic Therapiesmentioning
confidence: 89%
“…The median OS of the sorafenib/regorafenib sequence (considered from the beginning of sorafenib) was 28.8 months. All regorafenib-treated patients experienced side effects, but adverse events (grade ≥ 3) were severe in 14 patients (38.9%) [170]. Currently, no data except for case reports [171] are available for other recently approved tyrosine kinase inhibitors (lenvatinib [172] and cabozantinib [173]) and monoclonal antibodies (ramucirumab [174]).…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…The long survival time of 26 months achieved by timely sequential therapy is almost comparable to trae4ditional TACE in the treatment of intermediate-stage HCC (33,40). A recent study of patients with recurrent HCC after liver transplantation demonstrated that sequential therapy with sorafenib and regorafenib significantly prolonged OS (28.8 months), and was an independent predictor of OS (41). In recent years, some studies have found that nivolumab, cabozantinib, or regorafenib produce excellent treatment effects after sorafenib treatment failure in advanced HCC patients, but the difference was not statistically significant (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Regorafenib may be proposed as a second-line treatment in case of progression under sorafenib[ 71 ]. In a recent multicenter study, second line treatment with regorafenib after sorafenib discontinuation provided a median survival of 13.1 mo compared with 5.5 mo with best supportive care in post-LT HCC relapse[ 72 ]. Recently approved tyrosine kinase inhibitors (lenvatinib[ 73 ] and cabozantinib[ 74 ]) and monoclonal antibodies (ramucirumab[ 75 ]) will soon be introduced in clinical practice also for the treatment of post-LT recurrence, giving us the opportunity to collect data about their efficacy and toxicity in this setting[ 76 ].…”
Section: Treatment Of Post-lt Hcc Recurrencementioning
confidence: 99%